Parental positive affect and negative affect in same- and different-sex parent families: no associations with parental gender and caregiving role - Leter, Tamara L. M.; Ellis-Davies, Kate; Rubio, Bérengère; Vecho, Olivier; Bos, Henny M. W.; Lamb, Michael E.; Van Rijn – Van Gelderen, Loes (Frontiers in Psychology, 2024)
Positive and negative parental affect influence developing parent–child attachment relationships, especially during infancy as well as children’s social–emotional, academic, and behavioral functioning later in life. Increasingly, because both mothers and fathers can play central caregiving roles, the parenting qualities of both parents demand consideration. Therefore, this study investigated whether parental gender and caregiving role were associated with mothers’ and fathers’ positive affect and negative affect during interactions with their 4-month-old firstborn infant, while determining whether parenting stress, infant temperament, having a singleton/twin, and living in the Netherlands, France, or the United Kingdom were related to parental positive affect and negative affect. In all, 135 different-sex, same-sex male, and same-sex female couples (113 fathers and 157 mothers, comprising 147 primary, and 123 secondary caregivers) who conceived through artificial reproductive techniques were studied. The couples were videorecorded at home while in feeding, cleaning, and playing contexts to assess the levels of positive and negative parental affect. In addition, the couples completed questionnaires about their caregiving role, parenting stress, and the infants’ temperament. Mixed linear models indicated that the levels of positive and negative parental affect toward the infant in all contexts were not related to parental gender, caregiving role, the interaction between parental gender and caregiving role, parenting stress, infant temperament, or singleton/twin status. However, the target parental behaviors were related to the country of origin, suggesting differences among Dutch, French, and British parents. Overall, we found no evidence that gender or caregiving roles were associated with the levels of positive and negative affect shown by the parents.